2022
DOI: 10.1111/1759-7714.14429
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of EGFR+/METamp+ vs. EGFR+/METamp‐ untreated patients with advanced non‐small cell lung cancer

Abstract: Background: MET dysregulation has been implicated in the development of primary and secondary resistance to EGFR tyrosine kinase inhibitor (TKI) therapy. However, the clinicopathological characteristics and outcomes of patients harboring EGFRsensitive mutations and de novo MET amplifications still need to be explored. Methods: A total of 54 patients from our hospital with non-small cell lung cancer harboring EGFR-sensitive mutations and/or de novo MET amplifications were included in this study. Survival rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Results from two studies demonstrated a significant statistical association between MET amp and a higher proportion of programmed cell death protein 1 ligand (PD-L1) expression ( 25 , 35 ). Overall, most studies (8/10) found no statistical association between MET amp and a positive smoking history ( 24 , 26 , 27 , 32 , 33 , 44 , 45 , 47 , 50 , 51 ). Among two studies that evaluated patients with EGFR- mutant NSCLC who experienced progression on an EGFR-TKI, one study found that history of smoking was associated with a high probability of secondary MET amp (p=0.011), and one study found no association between smoking status and presence of MET amp (p=0.45) ( 24 , 27 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Results from two studies demonstrated a significant statistical association between MET amp and a higher proportion of programmed cell death protein 1 ligand (PD-L1) expression ( 25 , 35 ). Overall, most studies (8/10) found no statistical association between MET amp and a positive smoking history ( 24 , 26 , 27 , 32 , 33 , 44 , 45 , 47 , 50 , 51 ). Among two studies that evaluated patients with EGFR- mutant NSCLC who experienced progression on an EGFR-TKI, one study found that history of smoking was associated with a high probability of secondary MET amp (p=0.011), and one study found no association between smoking status and presence of MET amp (p=0.45) ( 24 , 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…A summary of results from 16 US- or non-US based studies that evaluated demographic and clinical characteristics of patients with NSCLC with or without MET amp is found in Supplementary Table 4 ( 24 27 , 29 , 32 , 33 , 35 37 , 44 47 , 50 , 51 ). Results from the identified studies show that the following characteristics were consistently considered not associated with MET amp (either primary, secondary, or not specified): age (11 studies), sex (11 studies), and NSCLC sub-type (adenocarcinoma vs non-adenocarcinoma, squamous cell carcinoma, or other; 6 studies) ( 24 , 26 , 27 , 32 , 33 , 36 , 44 , 45 , 47 , 50 , 51 ). Results from two studies demonstrated a significant statistical association between MET amp and a higher proportion of programmed cell death protein 1 ligand (PD-L1) expression ( 25 , 35 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PDO is also an important pre-clinical model for predicting the efficacy of targeted therapies and can be used for prospective adjuvant targeted therapy experiments to reduce treatment costs and improve success rates [ 63 ]. In preliminary studies, clinical outcomes were consistent with drug response in PDO models [ 64 ]. LUAD PDO carrying EGFR and BRAF mutations successfully captures the clinical response of the tumor to Dabrafenib/Trametinib combination therapy [ 4 ].…”
Section: Clinical Research and Drug Screening Based On Lung Cancer Pdomentioning
confidence: 90%